The rise and fall of the confederate government volume 2 - Davis, Jefferson (Garrett & Massie Incorporated Richmond, Virginia, 1938)
Davis devoted three years and extensive research to the writing of what he termed 'an historical sketch of the events which preceded and attended the struggle of the Southern states to maintain their existence and their rights as sovereign communities.' The result was this perceptive two-volume chronicle, covering the birth, life, and death of the Confederacy, from the Missouri Compromise in 1820 through the tumultuous events of the Civil War, to the readmission of the Southern States to the U.S. Congress in the late 1860s.
Includes index
Keywords: Confederate States of America History; Politics and government -- 1861-1865 -- United States; History -- Civil War, 1861-1865 -- United States